Surviving Hamlet: Female Trauma through the Lens of Judith Lewis Herman’s Theory - Li, Cha; Zhao, Qian (Text Matters: A Journal of Literature, Theory and Culture, 2025)
This article employs Judith Lewis Herman’s Trauma and Recovery Theory as a framework to explore the theme of female trauma in Shakespeare’s Hamlet, a play renowned for its intricate psychological depth. It analyzes the traumatic events experienced by the pivotal female characters, Queen Gertrude and Ophelia, examining their traumas, with specific focus on Gertrude’s inner struggles regarding remarriage and Ophelia’s trauma stemming from political manipulation and her lover’s betrayal. Symptoms such as hyperarousal, intrusion, and constriction observed in the female characters are scrutinized, as are the recovery efforts of both characters, in particular, Gertrude’s quest for stability and efforts at reconnection with Hamlet, as well as Ophelia’s remembrance and mourning process. Through close textual analysis and engagement with contemporary trauma scholarship, this article demonstrates that Shakespeare’s portrayal of female suffering offers nuanced insights into the interplay between personal trauma and social structures, while highlighting the limitations imposed on female recovery in a patriarchal context.